Antinociceptive effect of Nephelium lappaceum L. fruit peel and the participation of nitric oxide, opioid receptors, and ATP-sensitive potassium channels - Oliveira, Alan Santos; Biano, Laiza Santos; Palmeira, David Nascimento; Almeida, Damião Rabelo de; Lopes-Ferreira, Mônica; Kohlhoff, Markus; Sousa, Jordano Augusto Carvalho; Brandão, Geraldo Célio; Silva, Ana Mara de Oliveira e; Grespan, Renata; Camargo, Enilton Aparecido (Frontiers in Pharmacology, 2023)
Introduction:Nephelium lappaceum L. (Sapindaceae) is a plant known as rambutan. It is used for various purposes in traditional medicine. Objective: We aimed to evaluate the antinociceptive effects of the ethanol extract of the fruit peel of N. lappaceum (EENL), the mechanisms involved in these effects, and the acute toxicity in zebrafish. Methods: We performed chromatography coupled to mass spectrometry, acute toxicity assay in zebrafish, and evaluation in mice submitted to models of nociception and locomotor activity. Results: We identified (epi)-catechin, procyanidin B, and ellagic acid and its derivatives in EENL. We did not find any toxicity in zebrafish embryos incubated with EENL. The locomotor activity of mice submitted to oral pretreatment with EENL was not changed, but it reduced the abdominal constrictions induced by acetic acid, the licking/biting time in both the first and second phase of formalin testing and capsaicin testing, and carrageenan-induced paw mechanical allodynia. Oral pretreatment with EENL increased latency time in the hot plate test. This antinociceptive effect was significantly reversed by naloxone, L-arginine, and glibenclamide respectively showing the participation of opioid receptors, nitric oxide, and KATP channels as mediators of EENL-induced antinociception. Conclusion: EENL causes antinociception with the participation of opioid receptors, nitric oxide, and KATP channels, and is not toxic to zebrafish.